Empirical contrasting of talents retention between samples of China and Malaysia - Zheng, W.; Kaur, S.; Wei, J. (2009)
Intellectual property and intellectual capital became the critical components of wealth creation, and core employees of organization become more significant than ever. Especially, core employees with higher organizational performance characteristics are often entitled talent for their key networking status in creating the organizational intelligent capital values. In the field of talents' retention, empirical study of relationship-oriented between talents' performance and withdraw tendency by modeling is taking lead way in highlighting the talents' turnover mechanism. This study will integrate positive research from two different aspects which job specialty types and nationality between China and Malaysia to compared the significance and functional routes which are reflected by various talent retention factors, to reveal retention management policy which may influence the talent retention and performance decision-making.